Disseminated Histoplasmosis in a domestic cat in Costa Rica - Urbina, Andrea (2019)
Histoplasmosis occurs occasionally in cats with and without predisposing factors. A 3-year-old domestic male cat was referred to the Small and Wild Animal Hospital at the School of Veterinary Medicine of the National University of Costa Rica with hypothermia, weight loss, anorexia, and progressive chronic bilateral suppurative rhinitis. The patient died during clinical stabilization. A complete necropsy and histopathology were performed revealing granulomatous inflammation with multiple intracellular yeast-like structures compatible with Histoplasma spp. in several organs. Mycological culture of lung tissue was positive for Histoplasma capsulatum. Possible factors involved in this case are discussed.